SELF-EFFICACY: A NEW RESEARCH CONSTRUCT IN INDONESIAN ENGLISH TEACHERS STUDY - Awaluddin Syamsu (Universitas Islam Negeri Alauddin Makassar, 2017)
Due to the significance of self-efficacy, it has been becoming a research concern in many fields such as health, business and education. Self-efficacy is defined as a degree of someone’s belief to be able to deal with constrains to perform the given task well (Bandura, 1977). In education, there have been many studies conducted in self-efficacy. English teachers’ efficacy is one of the areas that has been become a concern for many researchers in EFL context due to its benefit to the teachers and students. This research is qualitative research with the observation data collection technique. There were three observation objects: TEFLIN Journal, Indonesia Journal of Applied Linguistics, and Google Scholar. The result of the observation indicated that there was no any topic regarding self-efficacy in Indonesian context in the two journals, TEFLIN Journal and Indonesian Journal of Applied Linguistics; however in the Google Scholar there were some self-efficacy researches in Indonesian context but the issues which were being discussed were not self-efficacy in English Teaching context. Therefore, English teachers’ sense of self-efficacy has not been a research area yet in the context of English teaching in Indonesia.